Occurrence of the cALAs gene in the BCCO Actinomycetes collection and cultivation improvements for the overproduction of secondary metabolites in soil associated Actinomycetes - Pulferer, Lisa (Jihočeská univerzita, 2021)
Metabolites produced by Bacteria are known to have a wide range of biological activities, which are applied in various fields, like medicine. Most of them are synthesized by members of the group Actinomycetes, in particular from the genus Streptomyces. This thesis deals with the screening process of various Streptomyces strains for a specific gene which is involved in the synthesis of a manumycin-like secondary metabolite. Another aspect discussed here is how the addition of agar to the fermentation media and the pH value can influence the synthesis of bioactive metabolites. To determine the effectiveness of the metabolites various experiments were conducted.
Occurrence of the cALAs gene in the BCCO Actinomycetes collection and cultivation improvements for the overproduction of secondary metabolites in soil associated Actinomycetes
Keywords: Actinomycetes; Streptomyces; Kutzneria; secondary metabolites; cyclizing 5-aminolevulinate synthase; antibacterial activity; Actinomycetes; Streptomyces; Kutzneria; secondary metabolites; cyclizing 5-aminolevulinate synthase; antibacterial activity